2019
DOI: 10.12659/msm.914348
|View full text |Cite|
|
Sign up to set email alerts
|

Ferruginol Diterpenoid Selectively Inhibits Human Thyroid Cancer Growth by Inducing Mitochondrial Dependent Apoptosis, Endogenous Reactive Oxygen Species (ROS) Production, Mitochondrial Membrane Potential Loss and Suppression of Mitogen-Activated Protein Kinase (MAPK) and PI3K/AKT Signaling Pathways

Abstract: Background Thyroid cancer causes considerable mortality and morbidity across the globe. Owing to the unavailability of biomarkers and the adverse effects of existing drugs, there is an urgent need to develop efficient chemotherapy for the treatment of thyroid cancers. Plants have served as exceptional source of drugs for the treatment of lethal diseases. The purpose of this study was to evaluate the anticancer effects of ferruginol against thyroid cancer cells. Material/Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…[ 55 ] Jiang et al [ 56 ] demonstrated that natural products could exert antitumor effect via regulating ERK/MAPK signaling pathway. Luo et al [ 57 ] suggested that human thyroid cancer cells MDA‐T32, when treated with ferruginol diterpenoid could induce apoptosis and mitochondrial membrane potential loss by suppressing MAPK signaling pathway. In this study, the phosphorylation level of MAPK component protein in Rh2‐treated cells was prominently increased in a dose‐dependent manner, indicating that Rh2 promoted the MAPK pathway in U20S cells.…”
Section: Discussionmentioning
confidence: 99%
“…[ 55 ] Jiang et al [ 56 ] demonstrated that natural products could exert antitumor effect via regulating ERK/MAPK signaling pathway. Luo et al [ 57 ] suggested that human thyroid cancer cells MDA‐T32, when treated with ferruginol diterpenoid could induce apoptosis and mitochondrial membrane potential loss by suppressing MAPK signaling pathway. In this study, the phosphorylation level of MAPK component protein in Rh2‐treated cells was prominently increased in a dose‐dependent manner, indicating that Rh2 promoted the MAPK pathway in U20S cells.…”
Section: Discussionmentioning
confidence: 99%
“…The anticancer activity of these diterpenoids have been attributed to their potential to induce reactive oxygen species (ROS), alteration of MMP, apoptosis, and cell cycle arrest 13 . A number of diterpenoids has been evaluated in cell line as well as in animal model and even in clinical trials for their anticancer activity.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that the PI3K/AKT pathway regulates inflammation and cell survival [21,22]. Activation of the PI3K/AKT pathway has been reported to induce inflammation and apoptosis of chondrocyte [23].…”
Section: Discussionmentioning
confidence: 99%